Evaluating the Quality of Life of 231 Children With Primary Nephrotic Syndrome and Assessing Parental Awareness of the Disease - Li, Na; Hao, Jia; Fu, Tong; Du, Yue (Frontiers in Pediatrics, 2021)
Objective: This study aims to investigate the quality of life of children with primary nephrotic syndrome (PNS), assess their parents’ disease awareness, and provide a basis for the comprehensive management of children with PNS. Methods: A total of 231 children with PNS who were hospitalized in the Department of Pediatric Renal Rheumatology and Immunology in the ShengJing Hospital of the China Medical University from March 2019 to October 2020 were selected as the study subjects. The subjects and their parents were surveyed via a disease education and communication WeChat group and online questionnaire to investigate the children’s quality of life, the needs of the parents, and their knowledge related to the disease. Results: In 93.51% of cases, the child’s quality of life was affected, with mild to moderate effects being the most frequent (90.47%). The lowest overall quality of life scores were recorded for children who had been diagnosed 1–3 y prior to inclusion in the study, and the scores plateaued thereafter. On the physical functioning scale, the longer the illness, the greater the physical impact, with children typically experiencing pain and fatigue. The children generally scored low on the emotional functioning scale, exhibiting sleep disturbances for up to five years and worrying about accidents. The children’s average score on the social functioning scale was high, with males achieving significantly higher scores (69.61 ± 25.42) than females (62.30 ± 27.51), and more than one-third of the children experiencing problems getting along with other teenagers and making friends. The primary problems expressed by parents were anxiety (59%), sadness (44%), fear (43%), and depression (40%), and several parents indicated that they struggled with issues of self-blame. Conclusion: PNS impacts the physical and psychological wellbeing of children suffering from the condition, significantly reduces their quality of life, and negatively impacts the psychological wellbeing of their parents. Therefore, children with PNS and their families need integrated management by doctors, nurses, dieticians, psychotherapists, educational institutions, and social stakeholders to improve their quality of life.